Synthesis and Characterization of Palm Shell Activated Carbon for Adsorption of Remazol Brilliant Violet 5R - Walny Nicha; Mohammad Wijaya M.; Hasri Hasri (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
This study aims to characterize activated carbon derived from palm shells treated with 10% H3PO4 and evaluate its effectiveness as an adsorbent for removing Remazol Brilliant Violet 5R (RBV5R) dye. The adsorption capacity of the activated carbon was assessed based on adsorption efficiency using a batch adsorption method. The experimental process included preparation, carbonization, chemical activation, characterization, and adsorption studies conducted using a continuous system. Scanning Electron Microscopy (SEM) analysis of the unactivated carbon revealed that the pores were partially obstructed by residual carbonized substances, resulting in narrower pore structures. In contrast, activation with 10% H3PO4 produced larger and cleaner pores due to the effective removal of surface residues. Fourier-transform infrared spectroscopy (FTIR) analysis of the raw carbon identified functional groups such as O–H, C=C, and C– H, while the activated carbon exhibited characteristic peaks corresponding to C=O, P–O, and P–OH groups. Surface area analysis indicated a significant increase from 2202.532 m2/g for the unactivated carbon to 5137.431 m2/g after activation. Adsorption studies demonstrated that both adsorbents achieved optimal dye removal performance at pH 3 and a contact time of 20 minutes. The unactivated carbon achieved an adsorption efficiency of 84.618% and an adsorption capacity of 6.346 mg/g, while the activated carbon exhibited identical efficiency and capacity values.